A chaotic PSO approach to multi-mode resource-constraint project scheduling with uncertainty. (14th July 2011) - Chen, Weiming; Xiao, Renbin; Lu, Hongzhi
In this paper, a new optimisation method based on chaotic particle swarm optimisation (CPSO) algorithm for solving multi-mode resource-constraint project scheduling problem (MRCPSP) under uncertainty is proposed. Fuzzy set theory is used to represent the uncertainties of activity duration. A searching technique using CPSO algorithm is adopted to search for the minimum of fuzzy project completion time. A case with uncertain activity duration is used to illustrate the performance of the proposed method. The result indicates that CPSO algorithm can assist project managers in selecting a schedule with the least possibility of being late in an uncertain scheduling environment.